From a hornet’s sting to immediate percutaneous coronary inter-vention; a case report of a patient with Kounis syndrome - Andro Kurtić; Mersiha Bačevac (Liječnički vjesnik, 2023)
Kounis syndrome (KS) presents as acute coronary syndrome caused by an allergic reacti-on or anaphylaxis. The mechanism of KS involves the release of inflammatory cytokines through mast cell activation leading to coronary artery vasospasm and atheromatous plaque erosion or rupture. There are three types of KS. Type I is an allergic vasospastic angina caused by dysfunctional epithelium of coronary arteries. Type II occurs in patients with underlying coronary diseases, in whom the allergic reaction leads to plaque erosion or rupture. Type III includes coronary artery stent thrombosis secondary to an allergic reacti-on.